Transition Zones at the Changing Coastal Terrestrial‐Aquatic Interface - Patel, Kaizad F.; Malhotra, Avni; Norris, Cooper G.; McKever, Sophia A.; Fields, Devon M.; Musci, Jared I.; Bandopadhyay, Sreejata; Bond‐Lamberty, Ben; Chen, Xingyuan; Day, Donnie J.; Doro, Kennedy O.; Fluet‐Chouinard, Etienne; et al. (Journal of geophysical research. Biogeosciences, 2025)
Coastal soils are a significant but highly uncertain component of global biogeochemical cycles. These systems experience spatial and temporal variability in biogeochemical processes, driven by marsh‐to‐upland gradients and hydrological fluctuations. These fluctuations make it difficult to understand and predict biogeochemical processes in these highly dynamic systems. We studied coastal soil biogeochemistry and its variability (a) at regional scales and (b) across transects from upland forest to marsh, in two contrasting regions—Lake Erie, a freshwater lacustrine system, and Chesapeake Bay, a saltwater estuarine system. Salinity‐related analytes were a key source of variability in soil biogeochemistry, not just in the saltwater system, but surprisingly, also in the freshwater system. We had hypothesized linear trends in biogeochemical parameters along the TAI—however, contrary to expectations, transition soils were not consistently intermediate between upland and marsh endmembers; the non‐monotonic trends of C, P, Fe along our transects suggest that these do not behave as expected and may be difficult to model and predict—thus these are key analytes to study in our regions. Rapidly changing soil factors across coastal gradients (e.g., Ca, K, CEC, and TS) may act as precursors to ecosystem shifts. Our comprehensive soil characterization represents a snapshot of a single timepoint of surface soils and provides essential data for mechanistic modeling of ecosystem dynamics across coastal transects. Plain Language Summary Coastal soils are important for global cycles of nutrients and chemicals, but their behavior is not well understood. These soils vary greatly both over space and time, influenced by changes from marsh to upland areas and by water movement and disturbances. We studied soil variability in two different regions: Lake Erie, a freshwater system, and Chesapeake Bay, a saltwater system. We found that salt‐related factors significantly affected soil variability in both areas, which was unexpected for the freshwater system. Surprisingly, transition zones between upland and marsh did not always have intermediate soil properties. Elements such as carbon (C), phosphorus (P), and iron (Fe) showed complex patterns in these transition zones. Understanding the rapid changes in these soil factors can help predict shifts in ecosystems. Our detailed study of coastal soils provides essential information for modeling and understanding how these ecosystems function and change. Key Points We investigated variability in soil biogeochemistry across coastal systems to determine key parameters that may be transferable across different coastal regions Analytes such as C, Fe, Al, and P are important sources of regional variability in soil chemistry Transition zones do not always represent the intermediate point along the upland‐to‐marsh gradient and often show unique biogeochemical properties